Ethical Implications of Artificial Intelligence Accessibility in the United Arab Emirates: Bridging the Digital Divide - Hassanien, Ahmed Rabie Mohamed; Patwa, Nitin; Bagheri, Noushin; Tabash, Mosab I. (International Review of Management and Marketing, 2025)
The swift progress of artificial intelligence (AI) brings forth significant ethical challenges, especially concerning equitable access and responsible use. This research investigates the ethical aspects of AI accessibility within the UAE, emphasizing how governance frameworks, strategic management tactics, technological advancements, and societal attitudes influence the ethical adoption of AI. Utilizing structural equation modeling (SEM) with ADANCO, the study assesses five primary hypotheses related to the impact of ethical AI frameworks, strategic leadership, decision-making instruments, cultural viewpoints, and emerging technologies on the responsible integration of AI. This research contributes to the ongoing discussion about narrowing the digital gap by underscoring the importance of regulatory coherence, collaboration across sectors, and education in AI ethics. Recommendations for future actions stress the necessity for policy improvements, interdisciplinary governance models, and ongoing evaluations of AI ethics to align technological innovations with the UAE’s long-term digital transformation goals.